Escape distance and escape latency following simulated rapid bird attacks in an Andean lizard, Phymaturus williamsi - Fava, Gustavo Alfredo (2018)
Predatory birds represent the greatest risk for many lizard species. However, little is known about the functional relationship between the escape distance and escape latency of lizards during a rapid bird attack. We hypothesised that escape latency and distance in the Andean lizard species Phymaturus williamsi would increase proportionally, but vary according to the means of escape. Over a three-year period we observed seven types of antipredatory behaviour in 98% P. williamsi lizards on simulated predatory bird attacks. Escape distance and latency were positively correlated. 65% of lizards emerged from their refuge within 2 min of an attack. All of these behaviours were positively correlated with escape latency and distance, although we found the former to be more precise. This study contributes to a better understanding of the general antipredatory behaviour in this species of Andean lizard, and will assist in future decisions concerning its conservation.